Energy in America : a tour of our fossil fuel culture and beyond - Kelley, Ingrid (Burlington, Vt. : University of Vermont Press ; Lebanon, NH : University Press of New England, 2008)
Scientists tell us we need to cut carbon emissions to forestall effects of global warming. Reducing fossil fuel use is the key, and energy experts are hard at work devising solutions to change the nation's energy sector to one that is clean and sustainable for the future. But what is this energy sector we have and how did it come about? This book tells this story, emphasizing that energy use has always been based on cultural factors as well as technology. It relates how coal, oil and natural gas built the nation from its beginning and created today's consumer culture. It continues with the rise of the electric utility industry and its influence on American society. Finally, it explores the 1970s, when America woke to conservation and efficiency, and the renewable energy industries were born. It concludes with a look at the future possibilities for community energy planning and current trends in sustainable energy policy.--From publisher description.
Acknowledgments -- Introduction -- 1. Fossil fuels -- Coal : the king -- Oil : king of the road -- Natural gas : modern miracle -- Uranium and nuclear power -- 2. The electricity grid -- 3. Efficiency and conservation : the science and art of using less -- 4. Renewable energy -- Solar energy -- Wind power -- Biomass energy sources -- Other non-fossil energy sources -- 5. Community energy and sustainability -- Energy and smart growth planning -- 6. Clean energy policy and the government role -- Appendix A. Energy connections to sustainability goals -- Appendix B. Timeline : seven generations of fossil fuels -- Appendix C. Glossary of electricity terms -- Index.
Includes bibliographical references and index.
Keywords: Fossil fuels -- United States; Renewable energy sources -- United States; Sustainable living -- United States; Energy conservation -- United States